Protected retrieval of a detached iliac branch device nosecone - Leonardo Pasquetti, MD; Edoardo Pasqui, MD; Giuseppe Galzerano, MD; Bruno Gargiulo, MD; Cecilia Molino, MD; Gianmarco de Donato, MD (Journal of Vascular Surgery Cases and Innovative Techniques)
The detachment of components of endovascular devices is a rare but potentially harmful complication. This report describes a clinical case of nosecone detachment from an iliac branch device delivery system during an aortoiliac aneurysm exclusion in a 73-year-old male patient. After correct deployment, the iliac branch device nosecone detached during the removal of the delivery system. The guidewire was snared from the contralateral side, and two long sheaths were advanced to trap and protect the fractured piece, ensuring nice alignment and enabling its safe removal. This case highlights key strategies for managing serious complications encountered during endovascular aortic repair.